PENGARUH PENDAPATAN ASLI DAERAH DAN DANA BAGI HASIL TERHADAP BELANJA MODAL PEMERINTAH PROVINSI DKI JAKARTA - yurianto yurianto; Akhmad Tantowi (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Capital expenditures by local governments are carried out in the context of procuring tangible fixed assets to finance the implementation of regional autonomy which ultimately aims to improve people's welfare. This study aims to investigate the effect of local revenue and revenue-sharing on capital expenditures in DKI Jakarta Province with the Autoregressive Distributed Lag (ARDL) approach using data for the period 1987-2020. The results of the study indicate that there is a long-term relationship between the capital expenditures of the DKI Jakarta Provincial Government and the variables of local revenue and revenue-sharing funds. In the long run and the short run, the capital expenditure development of the DKI Jakarta Provincial Government is significantly influenced by the level of local revenue and revenue-sharing funds. If there is a disturbance or shock to the balance, then about 74.02 percent of the imbalance that occurred in the previous period will return to the equilibrium point in the current period.